Original paperPercutaneous closure of the left atrial appendage for secondary prevention of stroke in patients with atrial fibrillation and contraindications to chronic anticoagulant therapy - Lasek-Bal, Anetta; Mizia-Stec, Katarzyna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Stroke accounts for approx. 90% of thromboembolic complications associated with atrial fibrillation. The use of oral anticoagulants is the most effective therapy but is associated with risk of haemorrhagic complications. Aim: In this article, we describe a series of patients with atrial fibrillation, cardiogenic stroke history, and contraindications for long-term anticoagulant therapy, in whom an alternative method – percutaneous closure of the left atrial appendage – was performed. Material and methods : Nine patients with atrial fibrillation and previous stroke were qualified for percutaneous closure of the left atrial appendage (5 men and 4 women, aged 45–78 years). Physical and neurological examinations were conducted in the qualification period, 1–3 days before the intervention, and 1–3 days and 1, 3, 6, 12, and 24 months following percutaneous closure of the left atrial appendage. Transoesophageal echocardiography was carried out in the qualification period, 1–3 days before the intervention, and at 1–3 days and 3 and 6 months following the procedure. Results: No complications were observed in the perioperative period and during the follow-up period of 16–31 months. Echocardiographic examinations showed that occluders were present in the appropriate positions. Conclusions : Percutaneous closure of the left atrial appendage can be an alternative form of secondary prevention of stroke in patients with atrial fibrillation and contraindications for long-term anticoagulant therapy or those who have problems managing drug treatment. Complex clinical assessment performed by a neuro-cardiac team allows safe and efficient invasive treatment.